Reciprocal regulation of LOXL2 and HIF1α drives the Warburg effect to support pancreatic cancer aggressiveness - Rongkun Li (Nature Publishing Group, 2021)
Abstract Hypoxic microenvironment is common in solid tumors, particularly in pancreatic ductal adenocarcinoma (PDAC). The Warburg effect is known to facilitate cancer aggressiveness and has long been linked to hypoxia, yet the underlying mechanism remains largely unknown. In this study, we identify that lysyl oxidase-like 2 (LOXL2) is a hypoxia-responsive gene and is essential for the Warburg effect in PDAC. LOXL2 stabilizes hypoxia-inducible factor 1α (HIF1α) from prolyl hydroxylase (PHD)-dependent hydroxylation via hydrogen peroxide generation, thereby facilitating the transcription of multiple glycolytic genes. Therefore, a positive feedback loop exists between LOXL2 and HIF1α that facilitates glycolytic metabolism under hypoxia. Moreover, LOXL2 couples the Warburg effect to tumor growth and metastasis in PDAC. Hijacking glycolysis largely compromises LOXL2-induced oncogenic activities. Collectively, our results identify a hitherto unknown hypoxia-LOXL2-HIF1α axis in regulating the Warburg effect and provide an intriguing drug target for PDAC therapy.